MOTIVASI INDONESIA MENANDATANGANI SUBSIDIARY ARRANGEMENT PROGRAM MAMPU FASE II DENGAN AUSTRALIA TAHUN 2017 - Suryani, Sri Ok; Saeri, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aims to explain Indonesia’s interest signed MAMPU Program of Subsidiarry Arrangement, phase II whit Australia in 2017. Australia was chosen as partner in woman development section, therefore Australia has commitment to continue the good and powerful partnership of Australia and Indonesia’s government in the equal of gender and woman development. This subsidiary arrangement partnership was signed by both countries in January 2017, include increasing job condition and erasing discrimination in working area, increasing woman laborer for migrating to other country, increasing woman health and nutrient status, decreasing violence to woman, increasing acsess of social protection program of Indonesia. This research data was obtained from books, journals, articles, official document and websites that support the hypothesis. The author used liberalism approach from Immanuel Kant and international level analyze. The theories used in this research consist of international cooperation, international cooperative by Koesnadi Kartasasmita and K. J. Holsti, and national interest by Hans J. Morgenthau. The result of this research show that there is strengthening women development interest in Indonesia and Australia partnership that gives profit to Indonesia. This partnership gives large impact to woman development of Indonesia, especially through MAMPU Program. Australia could fulfill fund consideration for MAMPU Program in Indonesia, on quality and quantity scale. Keywords: National Interest, Woman Development, International Cooperative, Subsidiary Arrangement, MAMPU Program